Pengaruh Rapat Dewan Komisaris, Latar Belakang Pendidikan Dewan Komisaris Terhadap Nilai Perusahaan - Melisa Anggraini; Anoki Herdian Dito; Nila Fransiska; Dian Prasetyo Widyaningtyas Rahayu (Applied Research in Management and Business, 2021)
The application of the concept of corporate governance is an effort to restore the confidence of investors and institutions in the capital market. This research supports providing information about anything related to corporate governance in increasing firm value while consider the role of discretionary earnings management as a moderating variable in companies listed on the Indonesia Stock Exchange in 2015 - 2018. This analysis is also supported by several variables control variables there are company size and leverage. The results also show that discretionary earnings management is not able to moderate the relationship between the board of commissioners meeting and the educational background of the board of commissioners on the company's value.